Organisation der Kreditmarktfinanzierung in Italien - Glauco Della Porta (Kredit und Kapital, 1970)
Organization of Credit Market Financing in Italy The first section of this contribution deals with short-term credit and is introduced by a survey of the most important legal regulations and the instruments of the central bank (Banca d'Italia). Then the functions and peculiarities of the banks under public law, the supraregional private banks, the joint-stock and savings banks, and their respective central institutions are described successively. In the second section, following a detailed presentation of the statutory regulations governing medium and long term credit business, the organization of investment financing is described. Special consideration is given here to the financing problems of small and medium-sized firms. In particular, distinctions are made between the credit institutions according to their regional activity, the size of the borrowers and the degree of specialization.
Keywords: 330